(untitled) - Hornby, Albert Sydney (London, 1975)
This guide, written especially for students of english as a second or foreign language, explains and demonstraes the basic sentence patterns of contemporay english.
Keywords: English language,Tiếng Anh; Text-books for foreign speakers,Giáo trình dành cho người nước ngoài